Recurrent Spindle Cell Carcinoma Shows Features of Mesenchymal Stem Cells. (July 2018) - Ouchi, T.; Morikawa, S.; Shibata, S.; Takahashi, M.; Yoshikawa, M.; Soma, T.; Miyashita, H.; Muraoka, W.; Kameyama, K.; Kawana, H.; Arima, Y.; Saya, H.; et al.
This study investigated a case of spindle cell carcinoma (SpCC) in tongue pathological lesions. The patient experienced a local recurrence and distant metastasis after surgical intervention. Although standard chemotherapy was administered, a granulomatous mass continued to develop. This aggressive growth led to survival of the tumor. Secondary debulking surgery was performed to improve the patient's quality of life at the request of the patient. Using a tissue sample derived from the secondary debulking surgery, we performed an analysis of the tumor's cell surface antigens, differentiation potential, metastatic ability, and inhibition potential by anticancer reagents. In vitro analysis revealed that the cell population grown under adherent culture conditions expressed the mesenchymal stem cell (MSC) markers CD73, CD90, and CD105. The cell line established from this SpCC contained colony-forming unit fibroblasts (CFU-Fs) and exhibited multipotent differentiation into several mesenchymal lineages, including bone, cartilage, and fat. The SpCC cells also displayed vigorous mobilization. These characteristics suggested that they had the differentiation potential of mesenchymal cells, especially MSCs, rather than that of epithelial cells. The surgical specimen analyzed in this study resisted the molecular target reagent cetuximab, which is an epidermal growth factor receptor inhibitor. This clinical insight revealed that chemotherapy-resistant SpCC cells have different characteristics compared to most other cancer cells, which are sensitive to cetuximab. Our cell death assay revealed that SpCC cell death was induced by the anticancer drug imatinib, which is known to inhibit protein tyrosine kinase activity of ABL, platelet-derived growth factor receptor α (PDGFRα), and KIT. Here, we report recurrent SpCC with characteristics of MSCs and potential for treatment with imatinib.